Volumetric Hierarchy and Urban Dominance of the Urban System Centers in Al-Muthanna Governorate - Dr. Maher Nasser Abdullah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to identify the problem of imbalance and hierarchical arrangement of urban centers in Muthanna Governorate , and it was found that there is a high population concentration in the city of Samawah, followed by the city of Al-Rumaitha and then Al-Khidr , and the possibility of a dominant city was examined through the law of the first city of Jefferson and the rule of rank and size for falseness and evidence of dominance. , and the application of the balance indicator of urban to see the size of the imbalance equilibrium in urban cities network , and it became clear from the analysis of the results do not apply base grade and size and the presence of the so - called city 's dominant ( Samawa ) as a result of social and administrative economic reasons , and for the purpose of finding a balance in the distribution of the population The population distribution and future direction for the year 2030 were verified, and the research ended with a set of proposals .